2010
DOI: 10.1007/s00253-010-3056-7
|View full text |Cite
|
Sign up to set email alerts
|

Lead induces oxidative stress and phenotypic markers of apoptosis in Saccharomyces cerevisiae

Abstract: In the present work, the mode of cell death induced by Pb in Saccharomyces cerevisiae was studied. Yeast cells Pb-exposed, up to 6 h, loss progressively the capacity to proliferate and maintained the membrane integrity evaluated by the fluorescent probes bis(1,3-dibutylbarbituric acid trimethine oxonol) and propidium iodide. Pb-induced death is an active process, requiring the participation of cellular metabolism, since the simultaneous addition of cycloheximide attenuated the loss of cell proliferation capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…4). The exposure of yeast cells to Pb for 6 h induced a loss of proliferation capacity with a small loss of membrane integrity, similarly to the one described in S. cerevisiae cells (Bussche and Soares 2011).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…4). The exposure of yeast cells to Pb for 6 h induced a loss of proliferation capacity with a small loss of membrane integrity, similarly to the one described in S. cerevisiae cells (Bussche and Soares 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Pb is classified as a priority pollutant by the US Environmental Protection Agency (US-EPA 2006) and can cause, in humans, blood and brain disorders (ATSDR 2007). In the yeast Saccharomyces cerevisiae, Pb inhibits assimilation of nutrients (Chen and Wang 2007) and metabolic activity (Van der Heggen et al 2010), decreases the intracellular level of reduced glutathione (Perez et al 2013) and induces oxidative stress (Bussche and Soares 2011;, DNA damage (Cui and Tang 2000;Yu et al 2009;Yuan and Tang 1999), loss of proliferation capacity (Soares et al 2003;Suh et al 1999) and cell death displaying phenotypic markers of apoptosis (Bussche and Soares 2011). Pb is compartmentalized in the vacuole by two parallel pathways: one dependent of H + gradient generated by the V-ATPAse and another mediated by ABCC transporters (Ycf1p, Vmr1p, Ybt1p and Bpt1p), after conjugation with glutathione, in a process catalysed by glutathione transferases 1 and 2 (Gtt1p and Gtt2p) (Sousa et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The exposition of S. cerevisiae cells to Pb resulted in a marked intracellular ROS accumulation [3]. GSH is the main redox buffer of the cells being a key factor against the oxidative stress and metals toxicity [25].…”
Section: Pb-induced Loss Of Viability In Wild-type and Glutathione-dementioning
confidence: 99%
“…In addition, it was shown that Pb induces the intracellular accumulation of reactive oxygen species (ROS), which can be the trigger of programmed cell death by apoptosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Once inside the cells, heavy metals can display several toxicity mechanisms which include oxidative stress, DNA oxidation and enzyme inhibition [3]. The exposure of yeast cells of Saccharomyces cerevisiae to Pb induced a loss of cell proliferation capacity [4,5], nuclear morphological alterations [6] and nuclear DNA damage [7][8][9]. In addition, Pb decreases the intracellular level of reduced glutathione [10] and induces the production of reactive oxygen species, which can be the trigger of programmed cell death by apoptosis [6].…”
Section: Introductionmentioning
confidence: 99%